if a/b+c=b/c+a=c/a+b than prove that (a^2/b+c)+(b^2/c+a)+(c^2/a+b)=0
Answers
Correct Question :--- if a/(b+c) + b/(c+a) + c/(a+b) = 1 ,, than prove that (a^2/b+c)+(b^2/c+a)+(c^2/a+b) = 0 ?
Solution :---
→ a/(b+c) + b/(c+a) + c/(a+b) = 1
Multiply LHS and RHS by (a+b+c) , we get,
→ a(a+b+c)/(b+c) + b(a+b+c)/(c+a) + c(a+b+c)/(a+b) = (a+b+c)
Now, lets see Numerator part First,
→ a(a+b+c) can be written as a²+a(b+c)= [ a²/(b+c) + a ]
similarly,
→ b(a+b+c) = b² + b(c+a)
→ c(a+b+c) = c² + c(a+b)
Putting these values in numerator , we can write ,
→ a² + a(b+c)/(b+c) = [ a²/(b+c) + a ]
→ b² + b(c+a)/(c+a) = [ b²/(c+a) + b ]
→ c² + c(a+b)/(a+b) = [ c²/(a+b) + c ]
____________________________
Putting these values now , we get,
→ [ a²/(b+c) + a ] + [ b²/(c+a) + b ] + [ c²/(a+b) + c ] = (a+b+c)
or,
→ [ a²/(b+c) + b²/(c+a) + c²/(a+b) ] + (a+b+c) = (a+b+c)
Now, we can see that, (a+b+c) will be cancel from Each side,
So, we get,
→ [ a²/(b+c) + b²/(c+a) + c²/(a+b) ] = 0